Analisis Penerapan Model Pembelajaran Blended Lerarning Masa Covid 19 di SMA Swasta Bandar Lampung - Mapful; Yoga Fernando Rizqi (Arden Jaya Publisher, 2022)
The Covid-19 pandemic has changed many aspects of human life today, especially in the world of education. To deal with this, there needs to be awareness from all elements engaged in education, looking for ways to adapt and continue the learning that is being carried out. The purpose of this study is to provide views or descriptions related to learning during the Covid-19 pandemic using a blended learning model. This research method uses descriptive qualitative analysis research methods. Descriptive analysis was carried out by monitoring student learning progress which was applied in other schools using the blended learning model. The results obtained in this study conclude that the use of the blended learning model has been widely applied in private schools, which is applied at the high school level.